Analysis of Promotion and Digital Marketing Strategies to Increase Sales - M. Trihudiyatmanto; Sukardi Sukardi (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - This study aims to determine the influence of promotional strategy and digital marketing on increasing sales at Focus Grafika Magelang. Method - The method used was quantitative with a statistical approach, utilizing primary data through questionnaires distributed to Focus Grafika Magelang customers. The population in this study was all Focus Grafika Magelang customers, with 80 respondents selected by accidental sampling. Data were analyzed using multiple linear regression equations with SPSS version 25 software. Findings - The results showed that promotional strategy and digital marketing had a positive and significant effect on increasing sales. Promotional strategy had a positive effect on sales growth, as evidenced by a significance value of 0.000 < 0.05 and a calculated t-value of 9.214 > t-table 1.992. Digital marketing had a positive effect on increasing sales, as evidenced by a significance value of 0.001 < 0.05 and a calculated t-value of 3.573 > t-table 1.992. Implications – This research can serve as a reference for managers to increase sales by maximizing promotional strategies and optimizing the use of digital marketing.